Cross-species validation of conserved miR-504/PDHA1 and miR-500/EGLN2 interactions in sheep oocyte development - Junzheng Zhang; Jie Wang; Hao Li; Keyu Fu; Xu Han; Shuang Ji; Yi Jin (Theriogenology, 2026)

From built-in LiDFP to high-stability interface: A targeted and persistent multistage strategy for lithium-rich cathode - Jin Zhu; Xiaosong Zhang; Denghui Ma; Lei Zhang; Yiyao Xiao; Keyu Zheng; Jiamin Duan; Shunjie Xu; Longhao Cao; Yinghui Li; Guanghua Guo; Xiuxia Zuo; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence” Aquaculture, Volume 622, 15 July 2026, 744082 - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

Seismic-attribute optimization for improving reservoir prediction integrating the spectral decomposition and automated machine learning - Keyu Ren; Wei Li; Lun Zhao; Wurong Wang; Jincai Wang; Han Wang; Yi Li; Linbo Qu; Dali Yue (Journal of Applied Geophysics, 2026)

Differential microbial communities and metabolite profiles in the rhizosphere and bulk soils of rubber tree (Hevea brasiliensis) infected with red root rot disease - Xiangjia Meng; Haibin Cai; Yongwei Fu; Keyu Bai; Lifang Zou; Cuicui Wang; Yi Zhou; Min Tu (Plant and Soil, 2026)

Projecting shifts in drought-induced thresholds for wheat yield loss under climate change in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Fangzheng Chen; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (Agricultural and Forest Meteorology, 2026)

First Case of Nocardia seriolae Infection in China Cultured Channel Catfish ( Ictalurus punctatus ) - Mingqi Ai; Keyu Zhou; Qibin Jiang; Kun Peng; Yilin Wang; Yiteng Luo; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Journal of Fish Diseases, 2026)
Nocardia seriolae is a causative agent for fish skin ulcers and sarcoidosis, resulting in significant losses in both brackish and freshwater fish farming industries. From October to November 2023, channel catfishes ( Ictalurus punctatus ) cultured in Xiaowan reservoir at Dali city, Yunnan province in China, showed gross pathological changes with skin ulcers, white nodules in the liver and heart, histopathological tests revealed the typical granulomas and chronic hepatitis changes in the liver, and the clumps of filamentous bacteria in the heart and spleen. A Gram‐positive acid‐fast bacterium (CCF_NS01) was isolated from viscera (liver, spleen and kidney); biochemical tests and 16sRNA‐GyrB gene concatenated sequences analysis of this isolated microorganism identified it as N. seriolae . Drug sensitivity testing indicated susceptibility to commonly used antibiotics such as co‐trimoxazole, doxycycline, enrofloxacin, florfenicol, amikacin and rifampicin. In isolated CCF_NS01, multiple pathogenic factors corresponding to encoding genes were detected, including espG , mftF , pcaA , fadD32 , pks13 , narJ , feoB , sodA , katG and mceF . 100% mortality with 1 × 10 8 , 1 × 10 7 and 1 × 10 6 cfu/mL in a 35‐d challenge test period was observed, and the intraperitoneal injection median lethal dose (LD 50 ) was 1.89 × 10 4 cfu/mL. This is the first isolation report of N. seriolae infection from cultured channel catfish, aiming to warn against the continuous host‐range expansion of this pathogen, which is threatening the inland aquaculture industry.

Modelling the socio-ecological security pattern for large freshwater lake regions: supply-demand mismatch in the Dongting lake area - Zhenyu Wang; Yuhao Gong; Le Xia; Keyu Luo; Tao Jiang; Yi Ying; Miaomiao Xie (Environment, Development and Sustainability, 2026)

Future climate change increases the risk of wheat yield loss due to agricultural drought in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (European Journal of Agronomy, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

Rejection of geosmin and 2-methylisoborneol by polyamide membranes in drinking water treatment: Performance-energy efficiency evaluation and practical implications - Yuanyuan Sun; Keyu Yao; Haowen Wu; Yi Tao; Liping Jiang; Jianhua Qiu; Hao Guo (Water Research, 2026)

Phenotypic and transcriptomic insights into the antibacterial effects of magnolol against the novel pathogen Vibrio misgurnus - Keyu Zhou; Qibin Jiang; Bowen Huang; Kun Peng; Mingqi Ai; Le Xu; Songmao Wu; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture International, 2025)

Myricetin, as a potential new antiviral agent against Rana grylio ranavirus (RGRV) - Kun Peng; Silu Tian; Le Xu; Yu Yuan; Mingqi Ai; Qibin Jiang; Keyu Zhou; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Fish & Shellfish Immunology, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Ferric uptake regulator (Fur) in Vibrio mimicus acts as an activator of citrate cycle and oxidative phosphorylation pathways, while enhancing virulence potential - Kun Peng; Keyu Zhou; Qibin Jiang; Yilin Wang; Mingqi Ai; Le Xu; Jiao Wang; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2025)

Investigation on catalytic distillation dehydrogenation of perhydro-benzyltoluene: Reaction kinetics, modeling and process analysis - Qinglian Wang; Keyu Le; Yi Lin; Wang Yin; Yixiong Lin; Maria V. Alekseeva; Vadim A. Yakovlev; Anton P. Koskin; Chen Yang; Ting Qiu (Chemical Engineering Journal, 2024)

Selective efficient photocatalytic degradation of antibiotics and direct Z-type migration pathway for hierarchical core–shell TiO2/g-C3N4 composites - Hu Liu; Jianmei Pan; Keyu E; Yi Guan; Wenbo Gou; Peng Wang; Shahid Hussain; Ze Du; Chengfei Ma (Environmental Science and Pollution Research, 2023)

Simultaneous adsorption and fluorescent detection of Cr(VI) via lanthanide coordinating polymeric porous microparticles - Qimeng Ran; Zilin Fan; Xinkai Guo; Xiulan Li; Keyu Yi; Xiaobo Liu; Kun Jia (Chemical Engineering Journal, 2023)